Pengaruh Pengkayaan PUN – 11 (Perikanan Unaya 2011) dengan Limbah Sawi terhadap Jumlah Populasi Cacing Sutra (Tubifex sp.) - Muhammad Dimas Alfiansyah; Azwar Thaib; Nurhayati Nurhayati (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The success of cultivation is influenced by several aspects, one of which is the natural food in the hatchery or fish larvae phase. One type of natural feed that is suitable for fish larvae is silk worms (Tubifex sp.). But the availability of silk worms is still very limited, so further culture is needed. This study aims to determine the effect of PUN-11 enrichment with mustard greens waste on the growth of silkworm populations. The design used in this study was a comparative design consisting of 2 treatments and 3 replications. The treatments used were P1 (PUN = 11%) and P2 (PUN = 11%) + mustard greens waste (10%). The results showed that the highest population of silk worms (Tubifex sp.) was obtained in treatment P2 (PUN: 11 90% + mustard greens waste 10%), which was 3105 ind/cm2, and the lowest number of silk worms was in treatment P1 (PUN: 11 100%), which is 2868 ind/cm2. The results showed that the T test showed that P2 had a significantly different effect (P > 0.05) on the silkworm population growth.